Reversing Hemianopia by Multisensory Training Under Anesthesia - Jiang, Huai; Rowland, Benjamin A.; Stein, Barry E. (Frontiers in Systems Neuroscience, 2020)
Hemianopia is characterized by blindness in one half of the visual field, and is a common consequence of stroke and unilateral injury to visual cortex. There are few effective rehabilitative strategies that can relieve it. Using the cat as an animal model of hemianopia, we found that blindness induced by lesions targeting all contiguous areas of visual cortex could be rapidly reversed by a non-invasive, multisensory (auditory-visual) exposure procedure even while animals were anesthetized. Surprisingly few trials were required to reinstate vision in the previously blind hemisphere. That rehabilitation was possible under anesthesia indicates that the visuomotor behaviors commonly believed to be essential are not required for this recovery, nor are factors such as attention, motivation, reward, or the various other cognitive features that are generally thought to facilitate neuro-rehabilitative therapies.